A Prevalence Estimation of Exstrophy and Epispadias in Germany From Public Health Insurance Data - Ebert, Anne-Karoline; Zwink, Nadine; Reutter, Heiko Martin; Jenetzky, Ekkehart (Frontiers in Pediatrics, 2021)
Introduction: The prevalence of rare diseases is very important for health care research. According to the EUROCAT registers the live prevalence for exstrophy and/or epispadias (grade 1-3) is reported with 1:23,255 (95% CI: 1:26,316; 1:20,000). A Europe-wide prevalence evaluation based on reports from excellence centers estimate a prevalence for exstrophies of 1:32,200 and for isolated epispadias of 1:96,800 in 2010. However the frequency of exstrophy (ICD-10: Q64.1) and epispadias (ICD-10: Q64.0) treated in different age groups in Germany remains unclear. Material and method: In accordance to the German Social Insurance Code, German institute for medical documentation and information (DIMDI) provides health care data of 71 million people with statutory health insurance (approx. 87% of the population) for research purposes. An inquiry to DIMDI was made regarding the diagnoses exstrophy and epispadias between 2009 and 2011. As analyzed insurance data were robust over the years, averaged data are mentioned. Detailed subgroup analysis of small numbers was forbidden due to privacy protection. Results: Annually, 126 persons of all ages with epispadias and 244 with exstrophy are treated as inpatients. In the observed population, 34 infant babies (<1 year of age) with epispadias and 19 with exstrophy (58% male) are treated as outpatients each year. This corresponds to an estimated live prevalence of 1:11,000 (95% CI: 1:14,700; 1:8,400) for EEC, more specifically a prevalence of 1:17,142 for epispadias and of 1:30,675 for exstrophy. The male-to-female ratio for exstrophy is 1.4:1 for infant babies and 1.6:1 for all minors. In children and adolescents, 349 epispadias and 393 exstrophies (up to the age of 17) are treated annually, whereas adults with exstrophy and even more with epispadias make comparatively less use of medical care. Conclusion: With the help of DIMDI data, live prevalence of bladder exstrophy and epispadias could be estimated. The prevalence of epispadias was higher than in previous reports, in which milder epispadias phenotypes (grade 1 or 2) may not have been included. These analyses might enlighten knowledge about nationwide incidence and treatment numbers of rare diseases such as the EEC.